Disturbance rejection control for PMSM using integral sliding mode based composite nonlinear feedback control with load observer. (October 2021) - Lu, En; Li, Wei; Wang, Shibo; Zhang, Wuguo; Luo, Chengming
Abstract: The low-speed high-torque permanent magnet synchronous motor (PMSM) drive system is a kind of typical nonlinear, strong-coupling and easy-parameter perturbation electromechanical coupling system. The control system is uncertainties and subject to unknown external interferences as well. In this paper, a disturbance rejection control method combining robust speed controller and load observer is proposed for low-speed high-torque PMSM. The robust speed controller combines the composite nonlinear feedback (CNF) which has advantage in improving the transient responsive performance and the integral sliding mode (ISM) advancing in improving system robustness. Subsequently, the effects of unknown external interferences are avoided by using a sliding mode observer (SMO), in which the chattering is reduced by introducing fuzzy control, and the observation is used for feed-forward compensation. The proposed robust speed controller solves the contradiction between the rapidity and overshoot of the traditional control method, and combines the load observer to compensate the influence of the load mutations and wide range of the load changes on the control system. Finally, the numerical simulation and experiments demonstrate that the proposed speed control method is able to achieve good transient performance in inhibiting system overshoot and reducing stable state error. Additionally, it successfully suppresses the influence of load disturbances and mutations, and shows the proposed method has better robustness. Highlights: There is no transmission mechanism in the permanent magnet direct drive system, various disturbances may seriously affect the speed control stability. The robust speed controller (ISM_CNF) is proposed to reduce the control system overshoot and address the parameter uncertainties and system disturbances. The fuzzy sliding mode observer (FSMO) is designed to observe load disturbances and mutations. The proposed disturbance rejection control method (ISM_CNF+FSMO) can achieve good transient performance in inhibiting system overshoot and reducing stable state error.